Memotret Wajah Ruang Publik melalui Sistem Penamaan Perumahan di Kota Malang: Kajian Lanskap Linguistik - Dany Ardhian; Eti Setiawati Eti; Millatuz Zakiyah Mila (Widyantara, 2023)
The naming system of residential areas serves not only as a strategy to influence consumers but also as a reflection of the characteristics, behaviors, lifestyles, and social motivations of a region's community. This research aims to investigate the forms and patterns of language usage, analyze collocation relationships, and examine the information-symbolic functions of language use. Data were collected from 257 texts on housing signs in five districts of Malang City: Lowokwaru, Klojen, Blimbing, Sukun, and Kedung Kandang. The data source for housing signs was collected using documentation techniques (photography). Interviews were conducted with a number of developers and homebuyers. The data were analyzed using corpus linguistics (LancsBox software version 6.0) and the linguistic landscape framework proposed by Landry and Bourhis. The research results indicate that five languages are involved in the residential naming system, namely Indonesian, English, Arabic, Spanish, and Japanese. The use of Indonesian and English is extensive in the housing naming system, and both languages are involved in all patterns, including monolingual, bilingual, and multilingual. Some other languages, such as Javanese, Arabic, and Japanese, are also present but in a more varied manner. Corpus linguistic analysis also shows that the lexicons "perum" (housing) and "residence" form a strong collocation relationship. The information function indicates that location, housing model, and aesthetic image are dominant. This situation leads to the naming patterns of housing being dependent on these three aspects. The language use symbols demonstrate modernity and exclusivity, collaborating with the symbols of urban lifestyles in Malang City, which still maintain a Javanese and Islamic nuance. Sistem penamaan perumahan tidak hanya menjadi strategi untuk memengaruhi konsumen, tetapi juga memotret karakteristik, perilaku, gaya hidup, dan motivasi sosial masyarakat suatu wilayah. Penelitian ini bertujuan menginvestigasi bentuk dan pola penggunaan bahasa, menganalisis relasi kolokasi, dan fungsi informasi-simbolis dari penggunaan bahasa. Data diambil dari 257 teks pada papan nama perumahan di lima kecamatan di Kota Malang, yaitu Lowokwaru, Klojen, Blimbing, Sukun, dan Kedung Kandang. Sumber data papan nama dikumpulkan dengan teknik dokumentasi. Wawancara dilakukan kepada sejumlah informan pengembang dan pembeli perumahan. Data dianalisis menggunakan linguistik korpus (software LancsBox versi 6.0) dan lanskap linguistik Landry dan Bourhis. Hasil penelitian menunjukkan lima bahasa terlibat dalam sistem penamaan perumahan, yaitu bahasa Indonesia, Inggris, Arab, Spanyol, dan Jepang. Penggunaan bahasa Indonesia dan Inggris masif pada sistem penamaan perumahan. Kedua bahasa ini terlibat dalam semua pola, baik monolingual, bilingual, maupun multilingual. Hasil analisis linguistik korpus juga menunjukkan bahwa leksikon perum dan residence membentuk relasi kolokasi yang sangat kuat. Fungsi informasi menunjukkan lokasi, model perumahan, dan citra keindahan muncul secara dominan. Simbol-simbol penggunaan bahasa menunjukkan modernitas dan eksklusivitas berkolaborasi dengan simbol perilaku masyarakat urban perkotaan di Kota Malang yang masih melekatkan nuansa Jawa dan Islam.